Literature Study: Burnout and Coping among Emergency Room Nurses - Ivana Sundari; Kurniawan Yudianto; Aan Nuraeni (Journal of Nursing Care, 2022)
Burnout is an emotional fatigue syndrome that often occurs on nurses in Emergency Department (ED). Emergency room nurses provide care quickly, responsively, and precisely. One of the factors that influence the burnout level is coping. Previous theories have not been able to explain positive coping for nurses who experience burnout, as well as literature review concerning burnout and coping among emergency room nurses are still minimal, so further research is needed.  This study aims to identify burnout and coping among emergency room nurses. This research is a narrative review. Conduct search for research articles in the CINAHL, Pubmed, Science Direct, and Google Scholar databases using "burnout" AND "coping" AND "emergency nurse" OR "perawat IGD." Inclusion criteria are articles on last ten years, primary research, sample of emergency nurses. Unrelevant articles are excluded. Thus, 19 relevant articles were obtained which were analysed using compare and contrast techniques. The results of this literature study found that emergency room nurses are prone to burnout, especially on emotional exhaustion dimension. Coping strategies that are often used by emergency room nurses are planful problem solving, seeking social support, and positive reappraisal which are effective coping in dealing with problems and modifying attitudes. Problem focused coping is associated with low risk of experiencing burnout. Training in the use of appropriate coping strategies in burnout prevention for emergency room nurses should be done so that work errors reduced and service quality improved.